Prognostic Value of Bcl-2 Expression in Squamous Cell Carcinoma of the Larynx: A Systematic Review. Issue 2 (April 2015) - Gioacchini, Federico Maria; Alicandri-Ciufelli, Matteo; Rubini, Corrado; Magliulo, Giuseppe; Re, Massimo
The aim of this systematic review was to determine the prognostic value of Bcl-2 immunostaining in patients affected by laryngeal squamous cell carcinoma. An appropriate search was conducted on PubMed to retrieve articles dealing with this topic. A double cross-check was performed on citations and full-text articles by 2 investigators independently to review all manuscripts and perform a comprehensive quality assessment. Of 115 abstracts identified, 15 articles were included. These studies reported on 1, 150 patients with histologically confirmed diagnosis of laryngeal squamous cell carcinoma. Only a few studies showed a statistical correlation between Bcl-2 immunohistochemical expression and at least 1 of the clinical and histopathological parameters considered by the authors. Moreover, these findings were also discordant between them. Overall the studies analyzed suggested that Bcl-2 expression was statistically connected with N stage (2/14), grading (2/14), disease-free survival (3/14) and overall survival (5/14). Interestingly, all of the 3 studies investigating the relation between Bcl-2 and radioresistance showed significant results in terms of recurrence-free survival and overall survival. Our review strongly suggests that the immunohistochemical staining of Bcl-2 does not correlate with tumoral aggressiveness and prognosis of patients affected by laryngeal squamous cell carcinoma and treated with primary surgery. However, an interesting connection of this protein could be demonstrated with tumoral radioresistance. Further, high-quality prospective studies should be carried out to confirm this hypothesis.